(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This paper attempts to present guidelines for improving the quality of life of students who are enrolled for the community development professional experience in Nakhon Si ThammaratRajabhat University during the 2019 coronavirus pandemic. The results of the study identified some guidelines based on the basic needs of the students. Students are advised to buy food from stores that follow strict preventive measures, eat homemade meals, and use separate eating utensils. If they are unable to cook food for themselves, they can order food from online platforms. They are advised to wear clean clothes. Used clothing should be washed immediately with disinfectants and dried in the sun. Houses should be cleaned frequently, and students should refrain from visiting friends and relatives. They should take care of their health, listen to the news, and enhance knowledge on the current crisis. Students should exercise daily at home, and if suspected of infection, they must coordinate with the community leaders to be transported to the nearest hospital. On the income front, they receive tuition fees from their parents, and some of them work for extra income to save enough for unexpected expenses. Despite the pandemic, students have managed to maintain social relationships. However, they should focus on the online mode of communication. While attending work in the community, body temperature should be checked and a face mask should always be worn. Washing hands frequently and social distancing are the key measures.